Clinically Meaningful Improvements in LUTS/BPH Severity in Men Treated with Silodosin Plus Hexanic Extract of Serenoa Repens or Silodosin Alone - Boeri, Luca (Sci Rep, 2017)
To assess the rate and predictors of clinically meaningful improvements (CMI) in patients with lower urinary tract symptoms (LUTS) treated with either silodosin (SIL) alone or with a combination of SIL+ serenoa repens (Ser) hexanic lipidosterolic extract for ≥12 months. Data from 186 patients were collected. Patients completed the International Prostatic Symptoms Score (IPSS) at baseline and at follow-up assessment. Descriptive statistics and logistic regression models tested rates and predictors of CMI. Two CMI were assessed: 1) >3 points improvement in total IPSS from baseline to end (CMI#1); 2) >25% IPSS improvement from baseline to end (CMI#2). Overall, 93 (50%) patients were treated with SIL and SIL+ Ser, respectively. At a mean 13.5-mos follow-up [range: 12–20], mean IPSS scores were significantly lower in patients treated with SIL + Ser compared to those after SIL (p = 0.002). SIL + Ser patients more frequently achieved CMI#1 (69.9% vs. 30.1%, p = 0.001) and CMI#2 (68.8% vs. 31.2%, p < 0.001) compared SIL men. At multivariable analyses, younger age, IPSS severity and SIL + Ser (all p < 0.03) were independent predictors of CMI#1 and CMI#2. In conclusion, SIL + Ser therapy was more effective than SIL alone in improving IPSS scores in men with LUTS. SIL + Ser treatment led to CMIs in up to seven out of ten men.